Assistive device for efficient intravitreal injections - Ullrich, Franziska; Michels, Stephan; Lehmann, Daniel; Pieters, Roel S.; Becker, Matthias; Nelson, Bradley J. (Ophthalmic Surgery, Lasers & Imaging Retina, 2016)
Intravitreal therapy is the most common treatment for many chronic ophthalmic diseases, such as age-related macular degeneration. Due to the increasing worldwide demand for intravitreal injections, there exists a need to render this medical procedure more time- And cost-efficient while increasing patient safety. The authors propose a medical assistive device that injects medication intravitreally. Compared to the manual intravitreal injection procedure, an automated device has the potential to increase safety for patients, decrease procedure times, allow for integrated data storage and documentation, and reduce costs for medical staff and expensive operating rooms. This work demonstrates the development of an assistive injection system that is coarsely positioned over the patient's head by the human operator, followed by automatic fine positioning and intravitreal injection through the pars plana. Several safety features, such as continuous eye tracking and iris recognition, have been implemented. The functioning system is demonstrated through ex vivo experiments with porcine eyes.
CRIS-Team Scopus Importer:2023-03-21